Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1099/ijs.0.63211-0
|View full text |Cite
|
Sign up to set email alerts
|

Haloferax sulfurifontis sp. nov., a halophilic archaeon isolated from a sulfide- and sulfur-rich spring

Abstract: A pleomorphic, extremely halophilic archaeon (strain M6 T ) was isolated from a sulfide-and sulfur-rich spring in south-western Oklahoma (USA). It formed small (0?8-1?0 mm), salmon pink, elevated colonies on agar medium. The strain grew in a wide range of NaCl concentrations (6 % to saturation) and required at least 1 mM Mg 2+ for growth. Strain M6 T was able to reduce sulfur to sulfide anaerobically. 16S rRNA gene sequence analysis indicated that strain M6 T belongs to the family Halobacteriaceae, genus Halof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 22 publications
0
26
0
3
Order By: Relevance
“…Salinity and depth vertical profile measurements have indicated that as spring water with low salinity diffuses to the banks of the stream, evaporation results in a decrease in moisture and an increase in salinity at the top soil layers, resulting in the creation of a microenvironment with higher salinity (24). Subsequently, multiple novel genera and species have been isolated from that location (25,58,59), some of which possess an exceptional ability to survive at low salt concentrations (58). As such, Zodletone Spring represents a moderate environment, well suited for the growth of mesophiles and extremely inhospitable to halophiles and where Halobacteriales survive in a distinct, narrow microenvironment within the top layers of the spring bank, which is constantly being diluted through the flowing spring water to the banks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Salinity and depth vertical profile measurements have indicated that as spring water with low salinity diffuses to the banks of the stream, evaporation results in a decrease in moisture and an increase in salinity at the top soil layers, resulting in the creation of a microenvironment with higher salinity (24). Subsequently, multiple novel genera and species have been isolated from that location (25,58,59), some of which possess an exceptional ability to survive at low salt concentrations (58). As such, Zodletone Spring represents a moderate environment, well suited for the growth of mesophiles and extremely inhospitable to halophiles and where Halobacteriales survive in a distinct, narrow microenvironment within the top layers of the spring bank, which is constantly being diluted through the flowing spring water to the banks.…”
Section: Methodsmentioning
confidence: 99%
“…Members of the genus Haloferax were present at Ͼ5% in CAR and MAN samples and at up to 17% in ZDT sample ( Table 2). Members of the genus Haloferax are widely distributed in nature, ranging from salt-saturated habitats to atypical low-salinity environments, e.g., Zodletone Spring (24,25). In addition, members of the genus Haloferax are often versatile, fast-growing microorganisms that are easily obtained in pure cultures (8) and have a wide range of substrate utilization and catabolic capabilities (27).…”
Section: Diversity Patterns In Halobacteriales Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Can these organisms use elemental sulfur, which may be very abundant, as the alternative terminal electron acceptor? This question was addressed several times in the past 30 years (Grant and Ross, 1986;Tindall and Trüper, 1986;Elshahed et al, 2004aElshahed et al, , 2004b, but no conclusive answer has been found. Acetate is an abundant electron donor and carbon source in anoxic habitats, which accumulates in the absence of high-potential electron acceptors, such as nitrate or ferric ion (Afshar et al, 1998;Kashevi et al, 2002;Slobodkina et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the extent of the family has been undergoing rapid expansion, with the description (as of June 2007) of five new genera and 20 novel species since 2006. This expansion has been due not only to the identification of novel taxa isolated from well-known hypersaline environments, such as the genera Halovivax, Halostagnicola, Haloplanus and Haloquadratum (Castillo et al, 2006a, b;Bardavid et al, 2007;Burns et al, 2007), but also to the recognition that members of the Halobacteriales can grow within saline microniches in non-saline environments at relatively low salt concentrations (Elshahed et al, 2004a;Savage et al, 2007). In addition, recent studies have reported the isolation of novel halobacterial strains (Purdy et al, 2004;Fukushima et al, 2007) or the detection of novel Halobacteriales-affiliated 16S rRNA gene sequences from moderate-to low-salinity systems (Munson et al, 1997;Takai et al, 2001;Walsh et al, 2005).…”
mentioning
confidence: 99%